2023
DOI: 10.1177/01492063231164969
|View full text |Cite
|
Sign up to set email alerts
|

Rising Every Time We Fall: Organizational Fortitude and Response to Adversities

Abstract: The role of organizational resilience enabling firms to respond to adversity and survive has become ever more critical in the wake of an increasingly unpredictable external environment. Yet, while we understand the importance of resilience in responding to a major adversity, we have little appreciation for how firms are affected and react when facing multiple adversities over time, or how multilevel factors might impose on this process. These are crucial issues given that adversities are not necessarily single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 74 publications
(192 reference statements)
0
11
0
Order By: Relevance
“…Referred to as "social capital" in the context of family business resilience (Nahapiet & Ghoshal, 1998;Stasa & Machek, 2022), the endowment of relational capability can be described as the reservoir of goodwill and robust relationships between family members and their external stakeholders, enabling them to facilitate actions and create value across generations (for a recent review on social capital, see Stasa & Machek, 2022). Social capital arises from history, trust, respect, loyalty, and altruism between family members, employees, and external stakeholders (Hammouda & Basly, 2020;Rodriguez et al, 2013;Smith et al, 2023) and can hence be seen as a consequence of family businesses' focus on long-term orientation and family values. 3 Studies on family business resilience have shown that family businesses with strong social capital are more likely to receive support from stakeholders (e.g., government, banks, and families) during difficult times, such as payment facilities or extended credit terms (Mahto et al, 2022).…”
Section: Theme 3: Resource and Capability Endowmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Referred to as "social capital" in the context of family business resilience (Nahapiet & Ghoshal, 1998;Stasa & Machek, 2022), the endowment of relational capability can be described as the reservoir of goodwill and robust relationships between family members and their external stakeholders, enabling them to facilitate actions and create value across generations (for a recent review on social capital, see Stasa & Machek, 2022). Social capital arises from history, trust, respect, loyalty, and altruism between family members, employees, and external stakeholders (Hammouda & Basly, 2020;Rodriguez et al, 2013;Smith et al, 2023) and can hence be seen as a consequence of family businesses' focus on long-term orientation and family values. 3 Studies on family business resilience have shown that family businesses with strong social capital are more likely to receive support from stakeholders (e.g., government, banks, and families) during difficult times, such as payment facilities or extended credit terms (Mahto et al, 2022).…”
Section: Theme 3: Resource and Capability Endowmentsmentioning
confidence: 99%
“…In sum, most former approaches focus on inherent attributes, rather than emphasizing dynamic processes (Luthar et al, 2000), which involve learning from crises and adapting positively (Beech et al, 2020). Recent research, however, supports a process view, recognizing resilience within a temporal context that includes reaction to adverse stimuli and subsequent coping efforts (Azouz et al, 2022; Smith et al, 2023). Furthermore, a definition that underlines the significance of different stakeholders, including the family, individuals (e.g., owner or owner-manager), and the organization itself is needed because family businesses often have intricate interdependencies among these units of analysis.…”
Section: Unveiling the Distinctive Dimensions Of Family Business Resi...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the third phase of organizational resilience, the intended postcrisis outcome can be a return to a state of normalcy or perhaps even a chance to bounce back better for facing competition-driven adversity (Smith et al, 2023).…”
Section: Organizational Resilience As a Processmentioning
confidence: 99%
“…this study revealed how strategic entrepreneurship research can advance a uniquely organizational understanding of resilience. Scholars increasingly recognize that measuring firm-level outcomes ex-post has resulted in disjointed theorizing about organizational resilience (Boin & van Eeten, 2013;Lengnick-Hall et al, 2011;Smith et al, 2023).…”
Section: Contributions To the Organizational Resilience Literaturementioning
confidence: 99%